2017
DOI: 10.21608/jacb.2017.38430
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Gene Action and Efficiency of Molecular Markers for Evaluation of Genetic Polymorphism for Orobanche Tolerance in Faba Bean (Vicia faba L.).

Abstract: The present study was carried out to identify the best cross(es) for Orobanche tolerance using genetic variance components and molecular analyses among four parents of faba bean, their six F 1 crosses and six F 2 populations which were produced via half-diallel mating design under Orobanche infected soil condition. Significant mean squares were recorded for parents and crosses for the studied traits. The GCA/SCA ratio was higher than unity for all studied traits, except for number of Orobanche spikes/plant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This difference may be due to the environmental variants and the genotypes adapting to dissimilar ecological conditions. These results agree with those obtained by Dora et al (2017) and Abdalla et al (2015). Positive and negative correlations occur through diverse morphological and agronomic traits (Singh et al 2017).…”
Section: Agronomical Traitssupporting
confidence: 94%
“…This difference may be due to the environmental variants and the genotypes adapting to dissimilar ecological conditions. These results agree with those obtained by Dora et al (2017) and Abdalla et al (2015). Positive and negative correlations occur through diverse morphological and agronomic traits (Singh et al 2017).…”
Section: Agronomical Traitssupporting
confidence: 94%
“…2014and Obiadalla-Ali et al 2015, who reported that the percentage of polymorphic bands detected ranged from 33% to 100% with an average of 66.47% and the average of amplified bands was 5.42 polymorphic bands per primer. Fifty four amplified fragments with sizes ranged from 113bp to 1647bp were obtained with an average of 10.8 loci per primer and the polymorphism percentage ranged from 50% to 100% with an average 81% (Dora et al, 2017) and 86.9% polymorphism obtained by Alghamdi (2009). While; 53.57% polymorphism percent and 140 bands with an average 7.77 bands per primer were obtained by Tahir (2015).…”
Section: Rapd Analysismentioning
confidence: 99%
“…were obtained by Basheer-Salimia et al 2013revealed that the genetic distance ranged from 0.069 to 0.358, with an average 0.213. And Dora et al (2017) reported genetic distance ranged from 0.099 to 0.556 on the basis of RAPD and SSR combined data among four faba bean genotypes and their seven F 2 bulks. The highest value indicates that the two genotypes are distantly related.…”
Section: Rapd Analysismentioning
confidence: 99%
See 2 more Smart Citations